Desain dan Implementasi Antena Quadrifilar Helix untuk Komunikasi Antarpulau pada Pita UHF - Heru Wijanarko; M. Hanif; Siti Aisyah; Kamarudin Kamarudin (Universitas Syiah Kuala, 2020)
Riau Islands, which consists of thousands of islands and is located in the border area of Indonesia, has its own challenges. Based on this strategic geographical location, there are threats and opportunities to develop inter-island information systems. Wireless long-range communication is considered the most suitable for these conditions. Antennas are an important part of wireless communication. Research and fabrication of the Helix Quadrifilar antenna by utilizing the advantages and consideration of simple, lightweight and inexpensive materials, as the receiver antenna in inter-island communication systems. In this research, the design was carried out with the assist of the Antenna Magus software, measurements were using a Vector Network Analyzer instrument, and testing accomplished under the LOS conditions. The results are fabricated antenna optimum frequency shift of 433 MHz to 452.5 MHz, within 5.88% error percentage. The antenna fabrication, which is measured at a frequency of 433 MHz, obtained return loss -13.06 dB and VSWR 1.5, that meets the criteria of 1 ≤ VSWR ≤ 2. Quadrifilar Helix Antenna fabricated results can receive data from GPS sensors, temperature, humidity, air pressure, wind speed and wind direction of up to 9 kilometers. So that this antenna is suitable to be used as an antenna for inter-island UHF communication.